“MISS RONA IS REALLY CLAPPING THE WHITE SUPREMACISTS”: BLACK TWITTER’S POLITICAL HUMOR IN COVID-19 TIMES - Antoine, Anshare Annie; Stanfill, Mel (AoIR Selected Papers of Internet Research, 2021)
As has been widely reported, the COVID-19 pandemic has disproportionately sickened and killed Black Americans. At the same time, however, there is a significant body of conversation on Black Twitter that jokes about the pandemic. This includes tweets that nickname the pandemic as "Miss Rona,” as in “god i need a drink so bad, miss rona i promise i will be good.” Through an analysis of tweets using the “Miss Rona” nickname, we examine how Black Twitter humor serves as a site of political critique of both public policy failures and the Trump administration more broadly, with users leveraging practices like Signifyin’, African American Vernacular English (AAVE), and wordplay to resist legibility by outsiders as they orient toward their own community. Black humor is political commentary that resonates with the Black community because the tweets address or refer to Black trauma during the pandemic: dealing with continued racial violence, white supremacist ideology, and medical disparities based on race. The tweets are also expressions of Black Twitter catharsis (joy despite pain) through witty one-sided Twitter banters that skillfully and playfully engage with several facets of the social and political climate. We consider how these conversations go beyond laughing to keep from crying to coded political statements and cultural alliance, and argue that Black Twitter’s jokes about the collective trauma of COVID-19 is a resource for online camaraderie, cultural critique, and community affiliation.